Effect of Foliar Application of Miyobi Growth Regulators on Morpho-Physiological Attributes and Yield in Chili - Rana, MIK; Mondal, MMA; Prodhan, AKMA; Azam, MG (Journal of Environmental Science and Natural Resources, 2012)
Miyobi solution sprayed on chili plants at 30 days after transplanting. Application of Miyobi increased plant height, branch and leaf number, root length, root number, root weight, stem weight, total dry matter, chlorophyll content and photosynthesis in leaves, fruits plant-1 and fruit yield over control. Reverse trend was also observed in fruit size. Most of the morphological, biochemical, yield attributes were increased with increasing Miyobi concentration up to 0.8 mgL-1 followed by a decline. These results indicate that application of Miyobi @ 1.1 mgL-1 may be toxic for plant growth and development. Control, where only water was sprayed, showed the lowest of the above parameters. The higher fruit yield was recorded in 0.5 and 0.8 mgL-1 with being the highest in 0.5 mgL-1 (369.8 g plant-1) due to increased number of fruits plant-1. The lowest fruit yield was recorded in control (260.3 g plant-1) due to inferiority in yield attributes. However, application of Miyobi at 0.8 mgL-1 was more costly than 0.5 mgL-1. Therefore, Miyobi with 0.5 mgL-1 may be applied for increased fruit yield of chili for further recommendation few more field trials will require. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10158 J. Environ. Sci. & Natural Resources, 4(2): 111-114, 2011